A positive feedback self-regulatory loop between miR-210 and HIF-1α mediated by CPEB2 is involved in trophoblast syncytialization: implication of trophoblast malfunction in preeclampsia - Wang, Hao; Zhao, Yangyu; Luo, Rongcan; Bian, Xiaotao; Wang, Yongqing; Shao, Xuan; Li, Yu-Xia; Liu, Ming; Wang, Yan-Ling (Biology of reproduction, 2020)
The pregnancy complication preeclampsia is directly associated with hypoxic stress and insufficient trophoblast cell differentiation. The hypoxia-inducible microRNA (miRNA), miR-210, has been identified as a significantly up-regulated miRNA in preeclamptic placenta, and evidence in other cell types has indicated a feedback regulation between miR-210 and hypoxia-inducible factor-1α (HIF-1α) under hypoxic condition. It remains unclear whether and how the feedback loop between miR-210 and HIF-1α may contribute to trophoblast dysfunction in preeclampsia. Here, we proved that cytoplasmic polyadenylation element-binding 2 (CPEB2) was a direct target of miR-210 in human trophoblast. CPEB2 could inhibit the translation of hypoxia-induced HIF-1α via directly binding the cytoplasmic polyadenylation element (CPE) site in the 3′-untranslated region (UTR) of HIF-1α mRNA. The increase in the HIF-1α level upon hypoxia treatment could be efficiently reversed by miR-210 inhibitor. In addition, CPEB2 was primarily expressed in villous syncytiotrophoblasts, and the suppression of trophoblast cell syncytialization by miR-210 could be significantly rescued by CPEB2 overexpression. In preeclamptic placenta, the expression of CPEB2 was evidently lower than normal pregnant control, and the miR-210 level was aberrantly higher and trophoblast syncytialization was limited. The findings revealed a positive feedback loop between miR-210 and HIF-1α that is mediated by CPEB2 in human trophoblasts, and demonstrated a mechanism underlying the insufficient trophoblast syncytialization in preeclampsia under hypoxic stress. Summary sentence A positive feedback loop between miR-210 and HIF-1α that is mediated by CPEB2 in human trophoblast demonstrates the mechanism of insufficient syncytialization in preeclampsia under hypoxic stress.